Odpowiedzi

Najlepsza Odpowiedź!
2010-03-25T19:21:41+01:00
A) delta=b(kwadrat)-4ac
delta=(-7)²-4*3*2
delta=49-24
delta=25
pierwiastek z delty=5
-b+pierwiastek z delty 7+5 12
x1=--------------------------=--------= ---=2
2a 2*3 6

-b-pierwiastek z delty 7-5 2
x2=--------------------------=--------= ---=1/3
2a 2*3 6


b)
delta=b(kwadrat)-4ac
delta=3²-4*4*(-1)
delta=9+16
delta=25
pierwiastek z delty=5
-b+pierwiastek z delty -3+5 2
x1=--------------------------=--------= ---=1/4
2a 2*4 8

-b-pierwiastek z delty -3-5 -8
x2=--------------------------=--------= ---=-1
2a 2*4 8
1 5 1